Myoglobin Cast Nephropathy Diagnosed on Renal Biopsy in a Patient Treated for Malarial Infection - Ramya Varadarajan; Ashmi Patel; Haneen Salah; Neil Sutaria; Roberto Barrios; Luan Truong; Lillian Gaber; Ziad M. El-Zaatari (Case Reports in Nephrology)
Myoglobin cast nephropathy occurs in cases of acute renal injury in which large amounts of myoglobin accumulate in the renal tubules, presenting as muscle pain, reddish-brown urine, and elevated creatine kinase levels. Our case describes a 60-year-old male who came to the emergency department with fevers, mild abdominal pain, and constitutional symptoms one day after returning to the United States from a trip to Nigeria. Initial workup demonstrated an acute kidney injury and elevated aminotransferase levels and the patient was started onatovaquone-proguanil for possible malaria given a recent diagnosis in Nigeria. Two days later, the patient was found to have rhabdomyolysis, resulting in a renal biopsy that showed myoglobin cast nephropathy. Previous literature has suggested mechanisms for the development of rhabdomyolysis in malarial infection, including inflammatory processes, direct effect of parasite accumulation, and drug-induced toxicity. Our case further implicates antimalarial therapy as a cause of rhabdomyolysis and increases awareness of myoglobin cast nephropathy as a potential complication of malaria.